2005
DOI: 10.1038/ng1589
|View full text |Cite
|
Sign up to set email alerts
|

An integrative genomics approach to infer causal associations between gene expression and disease

Abstract: A key goal of biomedical research is to elucidate the complex network of gene interactions underlying complex traits such as common human diseases. Here we detail a multistep procedure for identifying potential key drivers of complex traits that integrates DNA-variation and gene-expression data with other complex trait data in segregating mouse populations. Ordering gene expression traits relative to one another and relative to other complex traits is achieved by systematically testing whether variations in DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
1,007
0
7

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 957 publications
(1,041 citation statements)
references
References 47 publications
18
1,007
0
7
Order By: Relevance
“…We identified three loci on chromosomes 7, 17 and 18 that appear to be linked to metastasis-predictive ECM gene expression. Subsequently, correlation analysis was performed to facilitate candidate gene identification since the current prevailing hypothesis is that most modifiers are likely to result from modest variations in gene expression levels or mRNA stability [23,24]. This revealed a correlation between expression of a variety of genes within the peak region of linkage of each eQTL and the expression of various metastasis-predictive ECM genes (Supplementary Table 4 & Supplementary Table 5 and Crawford et al [10]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified three loci on chromosomes 7, 17 and 18 that appear to be linked to metastasis-predictive ECM gene expression. Subsequently, correlation analysis was performed to facilitate candidate gene identification since the current prevailing hypothesis is that most modifiers are likely to result from modest variations in gene expression levels or mRNA stability [23,24]. This revealed a correlation between expression of a variety of genes within the peak region of linkage of each eQTL and the expression of various metastasis-predictive ECM genes (Supplementary Table 4 & Supplementary Table 5 and Crawford et al [10]).…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analysis was performed to identify potential candidates for the chromosomes 7, 17 and 18 ECM modifiers since the current prevailing hypothesis that most modifiers are likely to result from modest variations in gene expression levels or mRNA stability [23,24]. Whole genome correlation analysis of the microarray data was performed using the Trait Correlation function of the WebQTL database within the GeneNetwork web service [18] to identify probe sets with high correlation coefficients with each of the ECM genes of interest.…”
Section: Identification Of Ecm Eqtl Candidate Genesmentioning
confidence: 99%
“…For example, by combining mapping of adiposity phenotypes with liver expression profiles in an F2 intercross, Zfp90, C3ar1 and Tgfbr2 were identified as causal for obesity. 12 From such studies, it is clear that some expression quantitative trait loci (QTLs), that is genetic loci regulating specific gene expression, colocalize with disease QTLs supporting that differentially expressed genes are causal for disease. 13 Schadt et al 13 have concluded that genes whose expression levels significantly correlate with a complex phenotype, transcript abundance are controlled by QTLs co-localizing with phenotypic QTLs and physical location are supported by phenotypic and expression QTLs are natural causal candidates for disease.…”
Section: Modern Approaches To Discover Adipose Tissue Genes Contributmentioning
confidence: 99%
“…To determine the degree of modularity and to identify the modules, we apply a random walk Markov CLustering algorithm (MCL) 5 [34,35] to the symmetric version, ) (s w , of the weight matrix, w. 6 The present network turns out to be highly modular (Modularity = 0.74 [37] where n is the number of modules. This reveals the global P-value of the graph theoretic modules being associated to coherent biological processes to be less than 5 10  , thus biologically validating the inferred modular architecture. More specifically, several (17) modules contain significant groups of genes involved in the same processes (P k < 0.01), e.g., biosynthesis, ribosome biogenesis and DNA replication.…”
Section: Modulesmentioning
confidence: 58%
“…This data is often analyzed by clustering over different experiments of wholegenome expression profiles, and that technique has provided important insights into gene function [2]. However, clustering alone cannot resolve gene interactions, and progress in network identification algorithms has revealed aspects of the static wiring of gene networks [3][4][5][6][7][8][9][10][11]. A recent study by Luscombe and colleagues [8] provided a first step towards an understanding of network dynamics by describing when different sub-networks are active during different cellular conditions in Yeast.…”
Section: Introductionmentioning
confidence: 99%